Synthesis, crystal and electronic structure of BaLixCd13–x (x ≈ 2) - Peng, Wanyue; Baranets, Sviatoslav; Bobev, Svilen (Frontiers in Chemistry, 2022)
A new ternary phase has been synthesized and structurally characterized. BaLixCd13–x (x ≈ 2) adopts the cubic NaZn13 structure type (space group Fm c, Pearson symbol cF112)) with unit cell parameter a = 13.5548(10) Å. Structure refinements from single-crystal X-ray diffraction data demonstrate that the Li atoms are exclusively found at the centers of the Cd12-icosahedra. Since a cubic BaCd13 phase does not exist, and the tetragonal BaCd11 is the most Cd-rich phase in the Ba–Cd system, BaLixCd13–x (x ≈ 2) has to be considered as a true ternary compound. As opposed to the typical electron count of ca. 27e- per formula unit for many known compounds with the NaZn13 structure type, BaLixCd13–x (x ≈ 2) only has ca. 26e-, suggesting that both electronic and geometric factors are at play. Finally, the bonding characteristics of the cubic BaLixCd13–x (x ≈ 2) and tetragonal BaCd11 are investigated using the TB-LMTO-ASA method, showing metallic-like behavior.